SISTEM INFORMASI PENGGAJIAN KARYAWAN DI SMK ISLAM SABILAL MUHTADIN DENGAN JAVA DAN MYSQL - Fiqry Fiqry; Afrinal Afrinal (Phasti: Jurnal Teknik Informatika Politeknik Hasnur, 2021)
Islamic Vocational High School (SMK) Sabilal Muhtadin Is One Of The Private Vocational Schools That Uses Islam As The Main Guideline For Religious Education But In The Process Of Calculating Employee Payrolls, It Is Still Manual Using A Calculator. This Is What Makes SMK Islam Sabilal Muhtadin Also Need A System That Can Manage The Data Contained Therein. This Is What Underlies The Author In Making Java And Mysql-Based Employee Payroll Information Systems. The Research Method Uses A Waterfall And System Design Is Carried Out Using UML (Usecase, Activity And Class Diagram).